Innovative Education: ChatGPT and the Right to Social Security in Nicaragua - Alemán-Madrigal, Luis Ernesto (Scientific journal of social studies, 2024)
In Nicaragua, the teaching of Social Security Law has lacked an interdisciplinary approach and the incorporation of technologies. This article proposes the feasibility of integrating artificial intelligence obstacles in its implementation, and offering recommendations for its integration into curricula. The incorporation of ChatGPT could be beneficial to improving the quality of education in the Nicaraguan legal field; however, a significant challenge is highlighted in awakening students’ interest in its use. The introduction of ChatGPT in the teaching of Social Security Law complements the teaching work and improves the learning process of students, representing an opportunity to enhance the quality of education in Nicaragua. These results suggest the importance of adopting innovative technologies in legal education to improve student training and keep up with advances in the field of artificial intelligence.in the teaching of this subject to contribute to the improvement of student learning. A mixed approach, combining quantitative and qualitative data, was used to evaluate the impact of ChatGPT on learning, identifying